Speed and Strength Test Instruments for Punch-Kick Combinations in Athletes - Muhamar Kodafi Putra; Ilham; Palmizal A; Atri Widowati (Journal of Education Reseach and Evaluation, 2025)
The available test instruments in pencak silat are still limited to manual methods, specifically by calculating each combination of movements visually within a specific time period. This, of course, yields less objective results and tends to be influenced by the observer's subjectivity. Based on this, the purpose of this study is to develop a sensor technology-based test instrument that can measure the speed and power of Punch-Kick combinations. This type of research involves research and development, utilizing the Borg and Gall development model, which is modified into 7 stages: potential problems, information collection, initial product design, expert validation, product revision, limited trials, and final product revisions. The research subjects are four experts from the field: one expert in sensor technology, one in pencak silat, one in test and measurement, and one in sports training. The trial subjects are 10 pencak silat athletes. The methods used in collecting data are observation, documentation studies, interviews, questionnaires, and tests. The instruments used to collect usable information are questionnaires. Data analysis techniques are qualitative and quantitative descriptive analysis. The results of the study are that the developed instrument has high validity and reliability. Validation with Aiken's V yields a value of 0.98, while the inter-rater reliability, as measured by Cronbach's Alpha, is 0.712, which is categorized as good. This demonstrates that the measuring instrument exhibits stability and reliability in measuring the Speed and Power of Punch-Kick Combinations. It is concluded that the developed pencak silat punch-kick combination speed and power test instrument is proven to be valid, effective, and significant for measuring the speed and power of punch-kick combinations.